ANALISIS DAN DESAIN KEMBALI UI GAME SMARTEST BRAIN MENGGUNAKAN METODE DESIGN THINKING - Anita Carolina Willyan; Mohammad Fajar; Baizul Zaman (STMIK KHARISMA Makassar, 2022)
This research aims to analyze and redesign the user interface of the educational game The Smartest Brain using the design thinking method in order to produce a user interface that increases children's interest in learning. Data was collected by distributing questionnaires to 20 respondents and processing data using the System Usability Scale method. Design thinking and System Usability Scale methods are used to produce a user interface design that is in accordance with the needs and desires of users, and to determine the usability level of a system. Based on the results of testing the first prototype using the System Usability Scale method, the score obtained is 72 with a Good rating. Meanwhile, based on the results of the second prototype test, the score obtained is 85 with an Excellent rating. Therefore, it can be concluded that designing the user interface using the design thinking method has solved the problems experienced by users, resulting in a user interface that is more attractive and easier to use, thereby increasing children's interest in learning.